Effects of support from organisations, host country nationals and spouses on expatriate success - Chan, Hak Liong (2016)
This study examined the effects of support from primary stakeholders, specifically organisations, host country nationals (HCNs) and spouses on expatriate success in Malaysia. Each stakeholder had a vital role to play in facilitating expatriates’ assignments in different manners. Malaysia was chosen as the research setting on account of its increasing number of multinational companies (MNCs) and international firms that strengthens the country’s economic growth. To see expatriate success in a wider angle, this study included the three essential criteria concerning cross-cultural adjustment, job performance and withdrawal intentions. In addition, Hobfoll’s conservation of resources (COR) theory was used as an overarching theory to complement and explain the research phenomenon with the key variables involved. A quantitative approach, employing a selfreporting questionnaire, was used to collect the data from the respondents. The whole data collection process took around three months to complete, and 112 expatriates working in different industries in Malaysia were surveyed. Multiple regression analyses were performed to test the six hypotheses. The results substantiated that support from both organisations and HCNs were significant to expatriates’ adjustment by helping them acclimatise to life in the host country. Notably, the findings of this research also indicated that support from organisations was the strongest predictor of the expatriates’ withdrawal intentions. This had highlighted that the crucial role organisations played in minimising the issue of expatriate failure during international assignment. The findings also revealed the significant relationships between expatriate adjustment, withdrawal intentions, and job performance. The discussion of these findings was teamed with interviews from five expatriates to cast some light on the understanding of the relationships. Finally, this research contributed to the area of international human resource and cross-cultural management, and subsequently provided additional solutions to practitioners.